The Impact of GDP, Investment, and Inflation on Poverty in ASEAN-8 Countries: A Panel Data Analysis (2010–2023) - Lalu Abu Gunawan; ismail pulungan; Feri Maulana Malik (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study examines the impact of Gross Domestic Product (GDP), investment, and inflation on poverty levels in eight ASEAN countries—Indonesia, Malaysia, the Philippines, Singapore, Thailand, Vietnam, Laos, and Cambodia—from 2010 to 2023. Despite rapid economic expansion in the region, poverty remains a persistent issue. Using panel data regression (Panel Least Squares) with 105 observations, the analysis assesses how these macroeconomic factors contribute to poverty reduction. The results show that the overall regression model is significant (Prob F-statistic = 0.000000), with an R-squared value of 0.3708, indicating that 37% of poverty variation is explained by GDP, investment, and inflation. Investment has the strongest and most significant negative effect on poverty (coefficient = –0.950933; p < 0.01), suggesting that higher investment effectively reduces poverty through job creation and productivity gains. GDP has a negative but insignificant effect (p = 0.0976), implying that economic growth alone does not automatically lower poverty without equitable distribution. Inflation shows a positive effect (coefficient = 0.747921; p = 0.0652), indicating that rising prices tend to worsen poverty by eroding purchasing power. These findings highlight the importance of promoting investment and maintaining price stability in ASEAN poverty-reduction strategies.